Customer Satisfaction with Service of Promise (Thailand) Limited. Bangkhae Plaza Branch, Bangkok - Naewkhamdee, Narathip; Thapchula, Krit; Angko, Daungjai (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
Research on customer satisfaction with services With the objectives 1) to study the level of customer satisfaction towards the service 2) compare the satisfaction of the customers with the service Providence (Thailand) Co., Ltd. Bang Khae Plaza Branch Bangkok The sample group consisted of 400 users of the service of Prosper Company using Convenience Sampling. The tools used to collect data were questionnaires. (Questionnaire) 2 parts. The statistics used are percentage, average ( ) and standard deviation (SD.) And hypothesis test statistics are t-test and One-Way ANOVA. The results of customer satisfaction levels towards the service provided by Promise (Thailand) Company Limited, Bang Khae Plaza Bangkok The overall level is at a high level with an average of (3.88) and the standard deviation is equal to (SD. = 0.678) when considered by each aspect, in order from the highest average score Found that the confidence With an average of (3.91), followed by care With an average of (3.89) reliability With the average value equal to (3.88), the concreteness of the service With an average of (3.87) and the response to the service recipients With an average value of (3.84). The comparison of customer satisfaction with the service provided by Promise (Thailand) Co., Ltd. Bang Khae Plaza Bangkok With personal characteristics such as gender, age, education level, occupation, average monthly income, found that there were statistically significant differences at 0.01 level Article history : Received 3 June 2019 Revised 23 June 2019 Accepted 25 June 2019 SIMILARITY INDEX = 0.00